The Use Of Drones To Solve Environmental Problems - Solokha, М. О. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 1970)
The article provides a method of aerial drones to monitor with dumps, pollution rate, river beds, monitoring benthos in the coastal zone of the sea. The examples of the use of UAVs in search of these objects. These legal aspects of the use of UAVs.